Bibliografia przekładów literatury słowackiej w Polsce w latach 2019-2020 - Buczek, Marta (Przekłady Literatur Słowiańskich, 2022)
The Bibliograpy of Translations of Slovak Literature in Poland presents translations of Slovak literature that appeared in Poland in 2019-2020, including translations of books and literature in magazines.